2018
DOI: 10.5194/bg-2018-290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biochemical and structural controls on the decomposition dynamics of boreal upland forest moss tissues

Abstract: Abstract.Mosses contribute an average of 20% of upland boreal forest net primary productivity and are frequently observed to degrade slowly compared to vascular plants. If this is caused primarily by the chemically complexity of their tissues, moss decomposition could exhibit high temperature sensitivity (measured as Q10) due to high activation energy, which would imply soil organic carbon (SOC) stocks derived from moss remains are especially vulnerable to decomposition with warming. Alternatively, the physica… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Notably, this study showed that the average SOC and soil TN contents of mosses in the shrub habitat were 133.35 g/kg and 9.99 g/kg, respectively; these values were significantly higher than the SOC and soil TN in the vegetated areas of the Maolan karst forest (54.72 g/kg and 4.67 g/kg) [ 33 ] and karst rocky desertification-affected secondary forests (80.40 g/kg and 2.80 g/kg) [ 32 ]. Mosses have a slower decomposition rate than vascular plants, resulting in high organic matter content in moss substrates [ 34 ]. Moreover, mosses can form symbiotic relationships with blue algae [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this study showed that the average SOC and soil TN contents of mosses in the shrub habitat were 133.35 g/kg and 9.99 g/kg, respectively; these values were significantly higher than the SOC and soil TN in the vegetated areas of the Maolan karst forest (54.72 g/kg and 4.67 g/kg) [ 33 ] and karst rocky desertification-affected secondary forests (80.40 g/kg and 2.80 g/kg) [ 32 ]. Mosses have a slower decomposition rate than vascular plants, resulting in high organic matter content in moss substrates [ 34 ]. Moreover, mosses can form symbiotic relationships with blue algae [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of sphagnan, which is a polysaccharide, could have contributed to higher shares of O‐alkyl, di‐O‐alkyl, hemicellulose and cellulose in the bog subsoils than in the fen subsoils. Furthermore, high shares of O‐alkyl are common in mosses (Maksimova et al., 2013; Philben et al., 2018), which are the dominant peat‐forming plants in bogs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, four adsorption–desorption cycles practically did not affect the magnetic separation of biosorbent ( Figure 11 ), confirming the very good stability of microwave synthesized nanoparticles and microparticles of iron oxides impregnated on the biomass surface also in an acidic environment (0.1 M HCl and 0.1 M CH 3 COOH), which is in agreement with the study of Wang et al [ 43 ]. Moreover, as was pointed out by Philben et al [ 44 ], the physical and chemical structure of moss cell walls cause their high persistence in the environment, and this could also contribute to their notable biocomposite stability.…”
Section: Resultsmentioning
confidence: 97%